Karakteristik dan Model Bimbingan Pendidikan Islam Bagi ABK Tunagrahita - Rahmandhani, Muhammad Arya; Rivadah, Migfar; Al-Husna, Yasmin Syarifah; Alamanda, Cerrila; Ridho, Muhammad Rasyid (Lembaga Yasin AlSys, 2021)
Research submitted on the mentally retarded crew is a person who really needs to be considered for its development because it has weaknesses in thinking and reasoning with this deficiency resulting in learning abilities and social adaptation below the average human being in general. This does not mean that they are unable to receive a proper education. There are various levels to assess the ability of mentally retarded children as seen from their characteristics, so that it can facilitate learning and educational institutions to identify learning models that will be used as in inclusive educational institutions so that they are right on target in increasing their knowledge, especially Islamic education. This study uses aresearch method library research which aims to examine the literature-based sources raised and look for a meaning from the characteristics and models that will be used in inclusive education.